IMPROVING STUDENTS’ ACHIEVEMENT IN READINGCOMPREHENSION THROUGH RECIPROCAL TEACHING STRATEGY - Hasmar Husein Lubis; Siti Aisah Ginting (Universitas Negeri Medan, 2014)
This study concerrns with Improving Students’ Achievement in Reading Comprehension Through Reciprocal Teaching Strategy. The objective was to investigate improvement of students’ achievement in reading comprehension through by applying reciprocal teaching strategy. This research was conducted by using action research method. The subject of the study was grade XI students of SMA NEGERI 1 SIABU MADINA totalling to 40 students. They were taught Reading by Reciprocal Teaching Strategy. The instruments for collecting data were quantitative data and qualitative data (observation sheet and questionnaire sheet). Based on the test score of quantitative data, students’ score kept improving in every evaluation. In the orientation test the mean was 57, 48, in the cycle I test the mean was 69, 75. In the cycle II test the mean was 81.28. The percentage of orientation test was 7, 50%, cycle I test was 15, 00% and cycle II test was 85, 00%. The finding of the research showed that applying Reciprocal Teaching Strategy significantly improved students’ achievement reading comprehension. The qualitative data show that the students were more interested and motivated on reading comprehension through achievement Reciprocal Teaching Strategy. It is suggested that teachers should apply Reciprocal Teaching Strategy as one of methods to improve students’ achievement in reading comprehension.